OPTIMIZATION PROBLEM OF LOWEST SAFETY FACTOR IN SLOPE STABILITY ANALYSIS AND THE SOLUTION USING MATLAB - KUSUMA ARI (NIM 12101024), ANOKO
Slope stability analysis can be determined using the limit equilibrium method which is commonly and usually used. Slope stability analysis using the limit equilibrium method can be analyzed by two steps: first, calculation of the safety factor of several particular trial slip surface then the safety factor is taken for the lowest one; and the other, directly searching for the lowest safety factor from a critical slip surface. All this time, considerable attention for determining the lowest safety factor has been given by trialing several slip surface and not seeing determination in minimizing the safety factor value as an optimization problem that supposed to be determined by the optimization method. Despitefully, there are several factors which influenced in calculating the safety factor, such as total of slope slice, base angle and normal effective strains on each slice. These are the problems why this research is done. Optimization of the lowest safety factor in this research which based on Bishop Simplified method, is analyzed using two kinds of optimization method, those are Genetic Algorithm and Quasi-Newton. Process is begun by numerical modelling of safety factor function problem, designing routine functions of the simulation program, and simulation of the program. This program which is named as DINI, is designed using MATLAB. Simulation process uses two kind of data model: 1st Model, dry slope condition, and 2nd Model, slope with phreatic surface. Result of the DINI subsequently is validated through several slope stability program such as GALENA and SSS (Saifuddin Arief, 1998). Result of the DINI simulation program, has minimum value than GALENA and SSS program, this case is due to the solution which analyzed by the optimization method formed as global optimum from several local minimum can be found. For the 1st Model, the safety factor value is gained at 1.479 (DINI) and 1.480 (GALENA), while for the 2nd Model, the value is gained at 0.980 (DINI) and 1.010 (GALENA).